SISTEM INFORMASI STRATEGIS MENDAYAGUNAKAN SISTEM INFORMASI UNTUK MENCAPAI KEUNGGULAN KOMPETITIF - Michael Iskandar (Bina Ekonomi, 2003)
While most companies are content to develop and implement computer-based information systems to improve their operational and managerial effectiveness, a few also rely on innovative systems to give them an edge over the competition. An information system that is specifically designed with the aim to create a competitive advantage for its firm is called a strategic information system.To build a strategic information system, one should have a good understanding as to what factors contribute towards competitive advantage. It is here that the analyses by Michael E. Porter on this subject are particularly invaluable. Furthermore, one should also realize what the modern computer excels at fast processing time, fast data retrieval, fast communications, and reliability.There are also risks inherent to strategic information systems. These include the large capital outlay involved, as well as the reality that any competitive advantage thus achieved is not sustainable for long.